A suggested best practices for enhancing performance of soft skills with entry-level hospitality managers. Issue 1 (2nd January 2020) - Weber, Melvin R.; Lee, Junghoon (Jay); Crawford, Alleah
ABSTRACT: As the nature of hospitality requires employees' having interpersonal or personal skills, the development of such soft skills has become one of the major topics among hospitality employers. The purpose of this research is to expand the findings of previous research on soft skill competencies and develop a practical model to assess differences between the importance and performance of soft skills. Importance/Performance Analysis was used to examine the differences in the perception of soft skills between managers and employees. An aggregate importance soft skill score of an HR expert was plotted with an aggregate performance soft skill score by an employee. This model further proposes using radial graphs to give individual feedback about soft skill competencies.